2009
DOI: 10.1152/ajpgi.00117.2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meal volume and calorie load on postprandial gastric function and emptying: studies under physiological conditions by combined fiber-optic pressure measurement and MRI

Abstract: This study assessed the effects of meal volume (MV) and calorie load (CL) on gastric function. MRI and a minimally invasive fiber-optic recording system (FORS) provided simultaneous measurement of gastric volume and pressure changes during gastric filling and emptying of a liquid nutrient meal in physiological conditions. The gastric response to 12 iso-osmolar MV-CL combinations of a multinutrient drink (MV: 200, 400, 600, 800 ml; CL: 200, 300, 400 kcal) was tested in 16 healthy subjects according to a factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
164
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(181 citation statements)
references
References 37 publications
13
164
0
Order By: Relevance
“…While the present study had no beverage only trial for direct comparisons, results from previous experiments suggest the consumption of food with fluid can enhance fluid retention (18,25). The consumption of food with fluid may result in higher nutrient and energy intakes and greater gastric distention, which together, are likely to delay gastric emptying (16). To date, only limited food items have been examined (rice/beef meal (18), beef jerky (25)) and on both occasions food and fluid intakes were prescribed.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…While the present study had no beverage only trial for direct comparisons, results from previous experiments suggest the consumption of food with fluid can enhance fluid retention (18,25). The consumption of food with fluid may result in higher nutrient and energy intakes and greater gastric distention, which together, are likely to delay gastric emptying (16). To date, only limited food items have been examined (rice/beef meal (18), beef jerky (25)) and on both occasions food and fluid intakes were prescribed.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
“…In this series, the median BT-OCTT was longer than 101 min obtained in a previous study in a large number of healthy volunteers in the seated position (26). An upright position may promote gastric emptying and bolus transit through the small intestine as documented by previous MRI studies (30,31); however any effect is likely to be small and unlikely to confound diagnosis of SIBO using the combined technique. Finally, inter observer agreement of MR-OCTT measurements was near perfect, but we did not test reproducibility of combined MRI-LHBT examination.…”
Section: Discussionmentioning
confidence: 44%
“…Scintigraphy has good sensitivity and specificity providing similar measurements of OCTT by using both solid and liquid meal (28), but is time consuming, relatively costly, sometimes difficult to interpret due to overlapping loops of small intestine and the caecum, and utilizes ionizing radiations (8,28). MRI was recently applied to evaluate GI structure and function (29)(30)(31) and to detect the presence of gas or liquids and the movement of fluid through the GI tract (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…They also found a further increase in the gastric volumes due to gastric secretions before the volumes started to decline. They found that this increase was independent of caloric load and greater for smaller rather than the larger infused meals [52].…”
Section: Physiological Parametersmentioning
confidence: 94%
“…The volume of liquid in the GI tract can affect the amount and potentially the concentration of the dissolved drug. Kwiatek et al [52] attributed a progressive decrease in initial gastric volume as a function of meal volume to a larger portion of liquid nutrient passing through the small intestine during a rapid early emptying phase. They also found a further increase in the gastric volumes due to gastric secretions before the volumes started to decline.…”
Section: Physiological Parametersmentioning
confidence: 99%